2011
DOI: 10.4161/jig.1.2.16828
|View full text |Cite
|
Sign up to set email alerts
|

Effects on confocal laser endomicroscopy image quality by different acriflavine concentrations

Abstract: BACKGROUND: Acriflavine is one of the commonly used staining agents in confocal laser endomicroscopy (CLE), a newly developed technique allows for real time histological observation of gastrointestinal mucosa, but the concentration is not unified. This study aimed to evaluate the effects of acriflavine with different concentrations on the CLE image quality and to find a sound concentration in clinical practice. METHODS: Twenty four consecutive patients who underwent upper gastrointestinal CLE were enrolled int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Consistent with the previous literature, AH crosses the cell membrane and displays a strong specificity for labelling acidic constituents [30,32,34,35]. It predominantly stains the nuclei of cells and has also been shown to demonstrate staining specificity for collagen and elastin.…”
Section: Image Interpretation Assessmentsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with the previous literature, AH crosses the cell membrane and displays a strong specificity for labelling acidic constituents [30,32,34,35]. It predominantly stains the nuclei of cells and has also been shown to demonstrate staining specificity for collagen and elastin.…”
Section: Image Interpretation Assessmentsupporting
confidence: 81%
“…Similarly, the linear and branching strands of collagen and elastic fibres are readily identified as structural constituents of normal fibrous connective tissue. It is worth noting that the most commonly used AH concentration reported in the literature is 0.05 % [30,32,[34][35][36]. We have shown that pCLE breast morphology is readily visualized at a concentration that is fivefold lower (0.01 %), than those in the published literature.…”
Section: Image Interpretation Assessmentmentioning
confidence: 74%
“…These techniques generate images of the tissue surface at resolutions of 1-2 micrometers and with a field-of-view of typically 500 micrometers. Most of these techniques rely on the use of either intravenous or topical contrast agents [16] (such as fluorescein or methylene blue) in order to enhance contrast. In some cases, the exogenous contrast agents are not required, such as in the lung since there is endogenous auto-fluorescence of the elastin within the endobronchial and the alveolar septal walls.…”
Section: A Background Of Endomicroscopymentioning
confidence: 99%
“…Over the last decade, it has found promising applications in the gastrointestinal tract, most notably during endoscopic surveillance of Barrett's esophagus [6], assessment of indeterminate biliary strictures [7] and in the lung [8]. Utilising intravenous fluorescein [6][7][8] or topical acriflavine [9][10] as the contrast agent, real-time confocal endomicroscopic image acquisition of in vivo tissue morphology is achieved through the process of optical sectioning which involves point-by-point illumination of the tissue surface using a rapidly scanning laser. Given the difficulties of miniaturizing devices for high speed laser scanning, an optical fibre bundle (confocal miniprobe) is used to relay the light source, typically a 488 nm wavelength blue laser, to the tissue surface and the resulting emissions from fluorescing tissues are collected between 500 and 650 nm and focused through a pinhole to block out-of-focus light.…”
Section: Introductionmentioning
confidence: 99%